2020
DOI: 10.3390/antiox9050445
|View full text |Cite
|
Sign up to set email alerts
|

One-Week High-Intensity Interval Training Increases Hippocampal Plasticity and Mitochondrial Content without Changes in Redox State

Abstract: Evidence suggests that physical exercise has effects on neuronal plasticity as well as overall brain health. This effect has been linked to exercise capacity in modulating the antioxidant status, when the oxidative stress is usually linked to the neuronal damage. Although high-intensity interval training (HIIT) is the training-trend worldwide, its effect on brain function is still unclear. Thus, we aimed to assess the neuroplasticity, mitochondrial, and redox status after one-week HIIT training. Male (C57Bl/6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Additionally, these authors found a reduction in CCL11 levels, a neurogenesis inhibitory marker, at the end of training reinforcing the potential role of HIIT in hippocampal neurogenesis. It has also been demonstrated that three sessions of HIIT induce an increase in cell proliferation in the hippocampus (minichromosome maintenance complex component 2 or MCM2), immature neuron content (doublecortin or DCX), BDNF and mitochondrial content (voltage-dependent anion-selective channel protein 2, VDAC) [ 121 ]. Additionally, a 7-week HIIT induces an increase in both cortical and hippocampal VEGF expression associated with a higher density of blood capillaries, but unfortunately, cognitive outcomes have not been measured [ 84 ].…”
Section: Do Hiit Promote Neuroplasticity and Cognitive Benefits Inmentioning
confidence: 99%
“…Additionally, these authors found a reduction in CCL11 levels, a neurogenesis inhibitory marker, at the end of training reinforcing the potential role of HIIT in hippocampal neurogenesis. It has also been demonstrated that three sessions of HIIT induce an increase in cell proliferation in the hippocampus (minichromosome maintenance complex component 2 or MCM2), immature neuron content (doublecortin or DCX), BDNF and mitochondrial content (voltage-dependent anion-selective channel protein 2, VDAC) [ 121 ]. Additionally, a 7-week HIIT induces an increase in both cortical and hippocampal VEGF expression associated with a higher density of blood capillaries, but unfortunately, cognitive outcomes have not been measured [ 84 ].…”
Section: Do Hiit Promote Neuroplasticity and Cognitive Benefits Inmentioning
confidence: 99%
“…Indeed, growing evidence has shown that high-intensity exercise can increase the level of BDNF, a critical nutritional factor promoting neuroplasticity, to a greater extent than MLIE (Jimenez-Maldonado et al, 2018;Rodriguez et al, 2018;Cefis et al, 2019). Other animal studies also highlight the positive effects of high-intensity exercise on the brain (Saucedo Marquez et al, 2015;Dos Santos et al, 2020;Hu et al, 2021).…”
Section: Can High-intensity Exercise Produce Equal Effects?mentioning
confidence: 99%
“…Studies have concluded that physical activity improves brain metabolism and cognitive function, but the brain region most significantly affected by exercise is the hippocampus [ 6 , 15 17 ]. The hippocampus is a key structure in the brain that is responsible for learning and memory [ 18 ], and appropriate exercise is responsible for an increased volume of blood flow to the hippocampus [ 17 , 19 , 20 ]. Although studies have shown that HIIT is an effective form of physical training, the neuroprotective effects on the hippocampus are not well understood.…”
Section: Introductionmentioning
confidence: 99%